Analysing the role of environment-related technologies and carbon emissions in emerging economies: a step towards sustainable development. Issue 3 (28th January 2022) - Hussain, Muzzammil; Mir, Ghulam Mustafa; Usman, Muhammad; Ye, Chengang; Mansoor, Sadia
ABSTRACT: The evaluation of the contribution of consumption-based carbon (CBCO2 ) emissions in greenhouse gas (GHG) emissions is crucially important for the design of sustainable environmental policies. Despite its importance, attention to the discussion of the role of environment-related technologies (ERT) in abating CBCO2 emission is limited. The role of ERT and renewable energy in reducing carbon emissions is investigated in a panel of seven emerging economies during 1990–2016 in the 'Environment Kuznets Curve (EKC)' framework. Cross-sectional dependence test, CIPS unit root test, Westerlund co-integration, and cross-sectional augmented autoregressive distributive lag econometric techniques are employed to support the propositions. Findings suggest the supportive role of environment-related technologies in the presence of renewable energy in reducing carbon emissions. However, GDP growth is substantially worsening the environment. The findings indicate the need to increase investment in environment-related technologies by the E-7 economies for a sustainable reduction in CB CO2 emissions. GRAPHICAL ABSTRACT: UF0001